Evaluation of the viability of microencapsulated Trichoderma longibrachiatum conidia as a strategy to prolong the shelf life of the fungus as a biological control agent - Arias-Chavarría, Luis Diego; Batista-Menezes, Diego; Orozco-Cayasso, Steffany; Vargas-Martínez, Alejandro; Vega-Baudrit, José Roberto; Montes de Oca-Vásquez, Gabriela (Frontiers in Chemistry, 2025)
Trichoderma is an antagonistic fungus used commercially; however, the viability of these formulations is affected by biotic and abiotic factors. In this research, microcapsules of sodium alginate reinforced with nanocellulose and/or chitosan were developed to encapsulate T. longibrachiatum conidia and characterized by SEM, FTIR, and TGA. The viability of the microencapsulated conidia was evaluated through different temperatures (room temperature, 5°C and 37°C), as well as their in vitro antagonistic potential against Fusarium oxysporum. The formulations evaluated had encapsulation efficiencies above 92% and the microcapsules with alginate, chitosan, and nanocellulose maintained 100% viability at 37°C for 2 months. In addition, all formulations evaluated retained antagonistic ability against F. oxysporum. These findings support the use of alginate, nanocellulose and chitosan for the formulation of microcapsules to maintain the viability of T. longibrachiatum conidia over time and at different temperature conditions.